2016
DOI: 10.5194/bg-13-4843-2016
|View full text |Cite
|
Sign up to set email alerts
|

Coccolithophore responses to environmental variability in the South China Sea: species composition and calcite content

Abstract: Abstract. Coccolithophore contributions to the global marine carbon cycle are regulated by the calcite content of their scales (coccoliths) and the relative cellular levels of photosynthesis and calcification rates. All three of these factors vary between coccolithophore species and with response to the growth environment. Here, water samples were collected in the northern basin of the South China Sea (SCS) during summer 2014 in order to examine how environmental variability influenced species composition and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 95 publications
4
30
0
Order By: Relevance
“…Hence, with information on the species (or morphotype) present and measurements of coccolith size it is possible to estimate coccolith calcite content (e.g. Poulton et al, 2011;Young et al, 2014;Jin et al, 2016). Together, these three metrics (cell-CF, coccolith calcite, coccolith production rates) allow for greater insight into the calcification of natural communities than can be obtained from bulk CP measurements alone.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, with information on the species (or morphotype) present and measurements of coccolith size it is possible to estimate coccolith calcite content (e.g. Poulton et al, 2011;Young et al, 2014;Jin et al, 2016). Together, these three metrics (cell-CF, coccolith calcite, coccolith production rates) allow for greater insight into the calcification of natural communities than can be obtained from bulk CP measurements alone.…”
mentioning
confidence: 99%
“…In order to examine changes in calcification, we made estimates of cellular coccolith production rates (Poulton et al, 2010(Poulton et al, , 2013Charalampopoulou et al, 2011) from cell-CF and estimates of coccolith calcite content using biometric A. Charalampopoulou et al: Coccolithophores across Drake Passage 5919 measurements Young et al, 2014;Jin et al, 2016). Examination of such trends in cellular calcification across environmental gradients allows for changes due to variability in both cell numbers and cellular calcification to be taken into account: bulk measurements of (community) CP may be driven by variability in both (Poulton et al, 2010.…”
mentioning
confidence: 99%
“…Coccolith assemblages were dominated by three species, Gephyrocapsa oceanica , Emiliania huxleyi , and Florisphaera profunda , comprising more than 98% of the total coccolith count (Figure S3 in the supporting information). F. profunda lives at a water depth interval of ~75–100 m, well below the deep chlorophyll maximum (DCM, ~60 m) in summer, thus indicating their deep water (lower photic) ecology in the SCS (Jin et al, ). Most of the Noëlaerhabdaceae coccolithophores' ( E. huxleyi and G. oceanica ) cells are found at the DCM depth, which also indicates that they are productivity representatives (Jin et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous living coccolithophore investigation indicated that both G. oceanica and E. huxleyi were the main contributors for the coccolithophore abundance that corresponded to the DCM in the water column (Jin et al, ). These two species were also found to be the predominant species in the upper photic assemblages in surface sediments of the SCS (Cheng & Wang, ; Fernando et al, ), indicating a high coccolithophore productivity and water fertility in the SCS basin (Jin et al, ). However, no subtle differences in the ecology of living G. oceanica and E. huxleyi populations were well documented in the study area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation